(untitled) (Asia Pacific Journal of Social Innovation, 2024)
This paper lists Mindanao’s indigenous and contemporary literatures by its third and fourth generation settlers published in local publications. The paper argues for the important place of the literatures of Mindanao in the national literature. Much has been studied of the literatures of Luzon and the Vizsayas but little attention is given to the literatures of Mindanao especially its indigenous works which, for a long time, had been regarded as anthropological antiquities than as literature. The present shift of government policy to emphasize the teaching of the literatures of the regions in the CHED-required subject, Philippine Literature all college students made literature teachers scramble for materials that are not yet available in published textbooks or in school libraries. The paper challenges scholars to further study the indigenous literatures of Mindanao in the hope of laying the groundwork for a Mindanao poetics and to follow through interdisciplinary studies of Mindanao’s .literatures in order to a clue of how a people’s present beliefs and practices began.